A Comparison of the Australian Colonoscopy Care Standards to Current Clinical Practice - Simona Sarmiento; Rikvin Singh; Jeremy Ripper; Kavitha Subramaniam (Health Science Reports)
ABSTRACT Introduction Colonoscopy remains the gold standard for colorectal cancer screening and surveillance. The Colonoscopy Clinical Care Standards were introduced by the Australian Commission on Safety and Quality in Healthcare to provide a national consensus on the benchmarks required for colonoscopy care in Australia. Despite these new guidelines being implemented, it is still unknown if they have been successfully adopted by hospitals in Australia. Methods This mixed‐methods study of outpatient colonoscopies from January to May 2022 compared the current clinical practice to the Colonoscopy Clinical Care Standards using quantitative and qualitative data. Thus, taking the first step to address this gap. Results In this single‐center study of adults (≥18 years of age) attending for an outpatient colonoscopy, there were 99 patients included with a mean age of 56 ± 15.2 years, and the majority of participants were female (56.6%). Only 21% of colonoscopies were considered “on time” for their corresponding triage category. An easily accessible documentation of informed consent for colonoscopy was available in 86% of cases. Bowel preparation was adequate in 88% of patients. Withdrawal time was reported in 14 patients and total procedure time was available for the majority (n = 92) of patients. Overall, a perceived benefit from colonoscopy (diagnostic findings or reassuring result of a normal colonoscopy) was determined in 93% of patients. Discussion This study has identified a number of areas that could be improved including documentation and availability, specifically of informed consent, discussion of risks and benefits, withdrawal time, timely colonoscopy, and adequate bowel preparation. In conclusion, recommendations would increase compliance with the Colonoscopy Clinical Care Standards, improve patient care and engage in best practice and can also be extrapolated to other healthcare providers.